Increasing quality of learning experience using augmented reality educational games - Videnovik, Maja; Trajkovik, Vladimir; Vibeke Kiønig, Linda; Vold, Tone (Springer US, 2020)
Adequate pedagogical approaches for integration of technology in the learning process create new opportunities for improving the quality of teaching and learning experiences, raising students’ interest and motivation for the classroom activities at the same time. Game-based learning implemented with different technologies can utilize students’ energy and enthusiasm for educational purposes. In order to increase the quality of experience of the learning process, elements of popular games (e.g., mobile games and augmented reality games) should be used in the educational context. This paper proposes methodological guideline that can be used for the integration of games in education. The methodological guideline defines the two steps process of creating educational games starting from students’ attitudes and needs, and then incorporates educational outcomes. As a case-study augmented reality educational games platform was designed in order to illustrate the possibilities and benefits of the proposed approach.
Keywords: Augmented reality educational games. Quality of experience of learning . Gamebased learning . Interactive learning environments